2022
DOI: 10.3390/su142316168
|View full text |Cite
|
Sign up to set email alerts
|

More Leadership, More Efficacy for Inclusive Practices? Exploring the Relationships between Distributed Leadership, Teacher Leadership, and Self-Efficacy among Inclusive Education Teachers in China

Abstract: In response to the need for facilitating the sustainable development of inclusive education, this study conducts a pioneering attempt to analyze the relationship between two types of school leadership, organizational (i.e., distributed leadership, DL) and individual (i.e., teacher leadership, TL), and teacher self-efficacy among inclusive education teachers in Mainland China. A total of 893 teachers from primary inclusive education schools in Beijing and Shenzhen, China, participated in this study. Structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 69 publications
2
6
1
Order By: Relevance
“…In particular, one important finding in a research study conducted in Spain by L opez-L opez et al (2021) on the degree to which school principals foster inclusion in compulsory education from the perspective of families, was the initiatives carried out by school principals to improve each school's openness to the community and the surrounding area. Furthermore, in a study conducted in China by Wang et al (2022), the school principals' distributed leadership included collaboration with the external support system. Also, L€ uddeckens et al (2022), in their study on school principals in Sweden on promoting inclusive education identified as a common practice the cooperation and working together with other stakeholders for creating relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, one important finding in a research study conducted in Spain by L opez-L opez et al (2021) on the degree to which school principals foster inclusion in compulsory education from the perspective of families, was the initiatives carried out by school principals to improve each school's openness to the community and the surrounding area. Furthermore, in a study conducted in China by Wang et al (2022), the school principals' distributed leadership included collaboration with the external support system. Also, L€ uddeckens et al (2022), in their study on school principals in Sweden on promoting inclusive education identified as a common practice the cooperation and working together with other stakeholders for creating relationships.…”
Section: Discussionmentioning
confidence: 99%
“…(2021) on the degree to which school principals foster inclusion in compulsory education from the perspective of families, was the initiatives carried out by school principals to improve each school's openness to the community and the surrounding area. Furthermore, in a study conducted in China by Wang et al. (2022), the school principals' distributed leadership included collaboration with the external support system.…”
Section: Discussionmentioning
confidence: 99%
“…However, the influence of distributed leadership on inclusive teaching practices seems to be divergent in the literature. On the one hand, while there have been few explorations on the effects of distributed leadership on such inclusive teaching practices as DI, relatively sufficient empirical evidence suggested positive connections between distributed leadership and different school organizational variables that may motivate educators' pedagogical improvement, including teacher leadership for inclusion, school supportive climate, faculty collaboration, teacher work engagement, and teacher efficacy [14,[33][34][35]. On the other hand, in the field of inclusive schooling, Mullick et al found that distributed leadership for inclusive education elevates the level at which educators become satisfied with their school working settings [36].…”
Section: Distributed Leadership (Dl) and The Employment Of DImentioning
confidence: 99%
“…The 22-item IETL scale validated by Wang et al was utilized to examine inclusive educators' perceptions of their leadership behaviors [14]. This scale was developed and validated in Chinese contexts for measuring inclusive teacher leaders' behaviors in five dimensions: advocating inclusive values (three items), implementing inclusive teaching practices (seven items), engaging in school-wide decision-making (four items), encouraging multilateral collaboration (four items), and liaising with an external support system (four items).…”
Section: Inclusive Education Teacher Leadership (Ietl) Scalementioning
confidence: 99%
See 1 more Smart Citation